2013
DOI: 10.3389/fncel.2013.00195
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms in epileptogenesis

Abstract: Epilepsy is a chronic brain disorder that affects 1% of the human population worldwide. Immune responses are implicated in seizure induction and the development of epilepsy. Pre-clinical and clinical evidence have accumulated to suggest a positive feedback cycle between brain inflammation and epileptogenesis. Prolonged or recurrent seizures and brain injuries lead to upregulation of proinflammatory cytokines and activated immune responses to further increase seizure susceptibility, promote neuronal excitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 112 publications
(132 reference statements)
0
78
0
3
Order By: Relevance
“…Neuroinflammation following seizures can both trigger brain dysfunction and serve as a potential target of therapy (24). Sookyong Koh described a positive feedback cycle between brain inflammation and epileptogenesis: seizures and brain injury increase inflammation, and those proinflammatory changes in turn heighten seizure susceptibility and neuronal excitability (25). Microglia are immune cells present in the brain that become activated rapidly with a brain injury such as seizure.…”
Section: Neurobiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation following seizures can both trigger brain dysfunction and serve as a potential target of therapy (24). Sookyong Koh described a positive feedback cycle between brain inflammation and epileptogenesis: seizures and brain injury increase inflammation, and those proinflammatory changes in turn heighten seizure susceptibility and neuronal excitability (25). Microglia are immune cells present in the brain that become activated rapidly with a brain injury such as seizure.…”
Section: Neurobiology and Pathogenesismentioning
confidence: 99%
“…In animal models, specific inflammatory pathways are being targeted to attenuate seizure-induced increases in inflammation-related genes as well as to decrease the susceptibility of animals to subsequent seizures. These mechanisms may well play a role in preventing epileptogenesis in the developing brain (25). For example, dexamethasone, minocycline treatment, and environmental enrichment all prevent the priming effect of early-life seizures on subsequent seizure susceptibility by retarding the activation of microglia.…”
Section: Neurobiology and Pathogenesismentioning
confidence: 99%
“…Epilepsy is a chronic neurological disease based on recurring seizures and accompanied by cognitive deficits and mood disorders in common, affecting 1% of the human population worldwide [33]. There is a positive feedback cycle between brain inflammation and epileptogenesis due to recurrent seizures and brain injuries that leads to stimulation of proinflamatory cytokines [33].…”
Section: Possible Role Of Gamma Delta T Cells In Epilepsy and Rementioning
confidence: 99%
“…There is a positive feedback cycle between brain inflammation and epileptogenesis due to recurrent seizures and brain injuries that leads to stimulation of proinflamatory cytokines [33]. Studies done so far have suggested that inflammation in the brain might advance epileptogenesis [33], however protective immune responses are also found in epilepsy besides other neurological diseases such as multiple sclerosis [33].…”
Section: Possible Role Of Gamma Delta T Cells In Epilepsy and Rementioning
confidence: 99%
“…Seizure activity elicits release of pro-inflammatory cytokines and activates immune responses. These phenomena have been widely related to an increased brain susceptibility to seizure, synaptic reorganization and neuronal death (Xu et al, 2013).…”
mentioning
confidence: 99%